التسامح في القرآن والسنة، وادعاءات المنكرين - Klaina, Mekki (Asian Journal of Islamic Studies and Da'wah, 2025)
The concept of al-Tasāmuh holds great significance in Islam, predating its discussion in the West and emphasizing coexistence within a framework of mutual respect and rights protection. This study examines al-Tasāmuh in the Quran and Sunnah, comparing it to the 1995 definition of Tolerance in foreign languages to clarify misconceptions that lead to distorted judgments about Islam. It highlights Islam’s broad scope of al-Tasāmuh, granting Muslims and non-Muslims the right to live peacefully, while distinguishing between human rights, which allow tolerance, and Allah’s rights, which remain non-negotiable. Research findings indicate that Tolerance has been inaccurately translated into Arabic, leading to misinterpretations, with studies confirming that Islamic al-Tasāmuh permits non-Muslims to live safely in Islamic society, provided they do not undermine its integrity. Critics of Islamic al-Tasāmuh often rely on inaccurate translations, linking it to secularism and detachment from religious and cultural identity. Furthermore, freedom has limits to prevent self-harm and harm to others. Islam does not impose religion, instead promoting dialogue and persuasion. To foster positive al-Tasāmuh, efforts should focus on educating future generations and enacting laws that protect all rights, ensuring that religious sanctities and moral values are not compromised. This study adopts an analytical and critical approach to provide a nuanced understanding of al-Tasāmuh in Islam.